Exergetic model of a small-scale, biomass-based CCHP/HP system for historic building structures. (December 2021) - Wegener, Moritz; Isalgue, Antonio; Malmquist, Anders; Martin, Andrew; Santarelli, Massimo; Arranz, Pol; Camarra, Oscar
Highlights: Methodology for exergy analysis of bio-solar CCHP/HP systems. Transient and dynamic model for optimal sizing of gasifier and other components. Optimal sizing can significantly reduce irreversibility losses. Biomass types have marginal effect on system exergy efficiency. Abstract: Biomass-based, small-scale Combined Cooling, Heating and Power (CCHP) systems can increase the energy autonomy of building complexes while reducing their Greenhouse Gases (GHG) emissions. In combination with air-to-water Heat Pumps (HP), highly efficient energy systems can be designed, which allow for high flexibility in serving thermal and electric demands. This study presents an exergy evaluation of such a small-scale CCHP/HP system using a dynamic modelling approach based on gasification of various types of woody biomass. The transient model takes into account the effects of the biomass chemical composition as well as of ambient temperatures on the exergy performance of all key components for various CCHP system sizes supporting an HP system. The model has been applied in a case study for a historic building complex, where the CCHP sub-system would support an HP-subsystem allowing for downsizing the latter. The results show that smaller CCHP systems operate with higher exergy efficiency, because for larger systems the heat transfer from the engine and the operation of the absorption chiller are less exergy efficient. The electric load-following CCHP subsystem reaches exergy efficiencies of up to 13.3%, indicating huge improvement potential for system and sub-system design. It was also found that the biomass composition heavily influences the exergy efficiency of the gasifier and in turn changes the exergy efficiency of the syngas engine and the entire CCHP sub-system.